(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this study, the effect of outdoor conditions (wind velocity and ambient temperature) on the thermal efficiency of a non-evacuated Compound Parabolic Concentrator solar collector (CPC) was investigated for two different flow rates. Matlab program was built, and simulation results for different outdoor conditions were compared with an actual outdoor data set that was taken at Misurata city, Libya. Although this study showed some effects of outdoor conditions on the CPC collector component’s temperatures and heat losses, no important influence on the collector efficiency was noticed. Therefore, even though wind velocity and ambient temperature vary throughout the day, approximating them as constant values is a reasonable assumption. Mass flow rate is the most important parameter that affects the CPC efficiency.